2023
DOI: 10.1029/2022gl102119
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Anisotropy in NW Namibia From XKS Splitting: Effects of Asthenospheric Flow, Lithospheric Structures, and Magmatic Underplating

Abstract: The opening of the South Atlantic oceanic basin is considered a classical example of a mantle plume-related continental breakup. The occurrence of the Paraná-Etendeka conjugate continental flood basalt (CFB) provinces (now in Uruguay and NW Namibia) is often assumed as evidence for the onset of the Gondwana breakup at ca. 130 Ma (Renne et al., 1992(Renne et al., , 1996Wilson, 1992). However, the role of mantle plume-plate interaction in the continental breakup and opening of the South Atlantic Ocean is still u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 66 publications
(100 reference statements)
0
5
0
Order By: Relevance
“…(2009) with additional results from Komeazi et al. (2023) and Ebinger et al. (2024), gridded in 0.5° bins, on the global tectonic map of Hasterok et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2009) with additional results from Komeazi et al. (2023) and Ebinger et al. (2024), gridded in 0.5° bins, on the global tectonic map of Hasterok et al.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Overview of existing azimuthal anisotropy measurements for the same region. Station-averaged teleseismic shear-wave splitting measurements from the updated compilation of Wüstefeld et al (2009), with additional data from Qaysi et al (2018), Komeazi et al (2023), and Ebinger et al (2024), are plotted in pink. The orientation and strength of anisotropy at 150 km depth from the anisotropic global surface wave tomography model 3D2018_08Sv (Debayle et al, 2016) is represented by the black bars.…”
Section: Introductionmentioning
confidence: 99%
“…To assess whether more than one anisotropic layer contributes to the observed shear wave splitting parameters, modeling the observations using two anisotropic layers was attempted. Because the back azimuthal data coverage for most stations is insufficient to constrain a two-layer model, we combined measurements from stations within the same terrane, including individual measurements from previous studies (e.g., Komeazi et al, 2023;Yu et al, 2015) (Figure S6 in Supporting Information S1). Individual "good" and "fair" quality non-null measurements for stations within a terrane (Figure S6 in Supporting Information S1) were stacked in bins covering a maximum range of 5-6°with respect to back azimuth and epicentral distance using the method of Wolfe and Earth and Space Science 10.1029/2023EA003469 Silver (1998), as implemented in StackSplit (Grund, 2017), yielding a single splitting measurement (ϕ and δt) for each bin.…”
Section: Methodsmentioning
confidence: 99%
“…Their results show a strong NE ϕ orientation, which they attributed to APM. Komeazi et al (2023) reported shear wave splitting measurements for stations in NW Namibia, attributing an observed NE ϕ direction to a combination of fossil anisotropy in the lithospheric mantle and anisotropy in the asthenosphere resulting from APM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation